Cotidiano em conflito: relações sociais e familiares de mulheres e escravos nos processos de divórcio em São Paulo (1780-1822) - Dias, Simone Merissi (2011)
The main objective of this research is to deepen, through the divorces processes, the conflicts immersed it the social and family life of slaves and women in the Capitania of São Paulo. For this purpose, it also analyzes the construction of the family and the social life of slaves, as well as those women that, after marriage in the Church, wanted to divorce. The stories told by these women to the ecclesiastical authorities at the right moment of breaking point of family alliance revealed some information about the relationship between women and the Catholic Church. Based on the research, were discussed the Church laws and relativity social impact of surveillance undertaken by the Catholic Church which consequently allowed to slaves and women to build social and family foundations, allowing questioning the stereotypes constructed about them